Psychological work in humanitarian emergencies in Haiti and Democratic Republic of Congo: some considerations based on two work experiences Intervenção psicológica em emergências humanitárias no Haiti e na República Democrática do Congo: considerações baseadas em duas experiências de trabalho - Ana Cecilia Andrade de Moraes Weintraub (Universidade de São Paulo, 2011)
Through the description of two examples of psychological interventions in humanitarian emergencies, this article aims to problematize the work of the psychologist in those situations. The concepts of "humanitarianism" and "emergency" are discussed based on two interventions made in Haiti and in the Democratic Republic of Congo. In both countries the mental health interventions happened inside a humanitarian organization and the objective of those interventions was to offer psychosocial support to the population of concern through a national mental health team. Cultural specificities, as well as theoretical and methodological challenges to the work of the psychologist in those situations are presented, especially those related to moral issues, to gender-based conflicts and to the insertion of the psychological work in a context where there is very little institutional support. Considerations related to theories and techniques of the area are presented, emphasizing the importance of interpreting the contents of the discourses taking into account the culture from where each person comes. Por meio da descrição de dois exemplos de intervenções de saúde mental em emergências humanitárias, esta reflexão visa problematizar o trabalho do psicólogo nestas situações. Os conceitos de "humanitário" e de "emergência" são discutidos à luz dos trabalhos realizados na República Democrática do Congo e no Haiti. Em ambos os países, as intervenções de saúde mental se deram por meio de uma organização humanitária internacional e nos dois casos, o objetivo era oferecer apoio psicológico à população em conjunto com uma equipe nacional formada por profissionais de diferentes áreas. Em ambos os casos, as especificidades culturais, assim como os desafios teóricos e metodológicos da ação do psicólogo são apresentados, notadamente as questões morais, de gênero e de inscrição do trabalho psicológico em contextos de grande carência de redes e de seguridade social. Por fim, são apresentadas considerações a respeito de algumas teorias e técnicas já descritas para este tipo de atuação psicológica, enfatizando-se a importância da escuta e da ressignificação dentro do contexto cultural de cada sujeito.